COMPARING SORPTION BEHAVIOR OF PYRETHROIDS BETWEEN FORMULATED AND NATURAL SEDIMENTS. (29th March 2013) - Cui, Xinyi; Gan, Jay
Abstract: Formulated sediments are recommended for use in toxicity tests to achieve standardized evaluations. However, the organic matter used in formulated sediments may differ qualitatively from that in natural sediments, which may lead to different chemical partition patterns and, hence, different toxicity effects. By deriving partition coefficients for organic carbon and dissolved organic carbon ( K OC and K DOC, respectively) for eight pyrethroid insecticides from three formulated and five natural sediments, the authors characterized the differences between formulated and natural sediments in pesticide sorption. For all pyrethroids, the mean values of K OC and K DOC of formulated sediments were two to three, and three to 10 times smaller than those of natural sediments, respectively. The two formulated sediments containing α‐cellulose or Manitoba peat showed significantly ( p  < 0.0001) smaller K OC and K DOC values than natural sediments based on statistical analyses, while the difference was not significant for the formulated sediment containing New Brunswick peat. The K OC values were closely correlated ( p  < 0.001) with soot carbon content, while the amount of carboxylic or phenolic functional groups may have affected K DOC . Therefore, the source and quality of organic matter are likely the most important factors in formulated sediments and must be standardized to provide consistency in sediment toxicity tests. Environ. Toxicol. Chem. 2013;32:1033–1039. © 2013 SETAC